(untitled) (Sociologisk Forskning, 2004)
It has been repeatedly argued by various Swedish experts and quoted in media, that parents only spend a few minutes in daily communication with their children. A quest for the source of this argument developed into an interest in both the phenomenon itself, and in the general understanding that adults of today are “poor” parents. The article has two aims, the first is to illustrate how this kind of “truth” is constructed and reproduced in arenas such as parents’ meetings and discussions in Swedish parliament, and the second to comment on the dominant Swedish discourse about poor parenthood, childhood and notions of risk. It is here argued that the statement about parents’ lack of time to talk with their children should be understood as a kind of contemporary urban legend/rumour that can both trigger and reproduce moral panic and strengthen adiscourse about weak parents. It is furthermore contended that a prerequisite for the acceptance of such rumours and moral panics as truth, is that they are coherent with an existing dominant discourse, in this case poor contact between parents and children.